Burnout dalam Memoderasi Pengaruh Persepsi Dukungan Organisasi terhadap Kesejahteraan Subjektif - Septiana, Sannia; Handayani, Ririn; Bastian, Adolf (CV. ITTC INDONESIA, 2025)
The spread of COVID-19 throughout the world has greatly affected the national and global economy. The research was conducted at the hospital. Awal Bros Ahmad Yani Pekanbaru with the aim of testing the role of burnout in moderating the influence of perceived organizational support on subjective well-being. The population of this study was 539 people. Based on this population size, in accordance with the Krejcie and Morgan (1970) table, the sample size for this study was 217 people. The sampling method used in this research is Systematic Random Sampling. All respondents will be used to obtain primary data related to the variables, which will be collected through a questionnaire with a 1-5 point Likert scale. All data obtained will be analyzed using Structural Equation Modeling (SEM) with the Smart PLS 3.0 analysis tool. This study found that perceived organizational support was positively related to subjective well-being; Burnout moderates the relationship between perceived organizational support and subjective well-being such that the relationship is strengthened when burnout is low.